Pendidikan Jasmani dan Olahraga: Dalam Hadis-Hadis tentang olahraga - Bunayar (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
The young generation is a valuable asset of a nation, so we must direct, guide and protect it as well as possible. The younger generation as well as the nation's cadres have a very big role in determining the progress and decline of a nation, even the independence of Indonesia cannot be separated from the role of the younger generation. The success of youth development as quality human resources and having competitive advantage is one of the keys to open opportunities for success in various sectors including education. While the long-term success is to build a developed nation. As stated by Basrowi that the success of youth development as quality human resources and having competitive advantage is one of the keys to opening opportunities for success in various other education sectors. In Islam itself, it not only teaches about prayer, fasting, and zakat, but also requires its adherents to be strong physically and spiritually. Islamic education not only teaches about faith, worship, morals, intellectuals but also teaches things related to health and physical strength, namely physical education. In fact, Allah loves the strong believer over the weak.